Strategy for Developing the UMAURIP Eco-Tourism Area in Timpag Village, Kerambitan District, Tabanan - Candranegara, I Made Wimas; Mirta, I Wayan; Jika, I Ketut; Putra, Kadek Agus Febriana (KnE Social Sciences, 2022)
Tourism has become a necessity for all levels of society. Therefore, tourism management must be done seriously by involving related parties. The Central Government and local governments issued several policies to support tourism development in Bali. The Bali Provincial Government through the policy and program direction implemented is the Vision ”Nangun Sat Kerthi Loka Bali” Which contains the meaning of maintaining the sanctity and harmony of Bali’s nature and its contents to realize a prosperous and happy Balinese manners life, from the scale to the life of Balinese manners and gumi in accordance with Bung Karno’s Trisakti principles, namely political sovereignty, economic independence, and personality in culture. Timpag Village is a village in Tabanan Regency, one of the programs rolled out in Timpag Village which is an innovative breakthrough, namely ”Umaurip, Utamaning Uma Lan Urip” with ecotourism development, namely developing the potential of Tourism Villages based on agricultural areas. With the main focus on developing owls (Tyto alba) which are friends of farmers in eradicating rat pests. The method used in this study is a mix method, which is a combination of qualitative research methods and reinforced with quantitative research methods. And the conclusion of this study briefly is that the Umaurip ecotourism area still prioritizes the development of ecotourism areas based on the community itself and there has been collaboration with various parties to advance the area, suggestions from researchers so that in the future this ecotourism area will be intensified in terms of promotion. so that many people know about the existence of this area. Keywords: Tourism, Umaurip, Ecotourism